2021
DOI: 10.1038/s41598-021-89982-y
|View full text |Cite
|
Sign up to set email alerts
|

The antagonistic Metschnikowia andauensis produces extracellular enzymes and pulcherrimin, whose production can be promoted by the culture factors

Abstract: Biological control against microbial infections has a great potential as an alternative approach instead of fungicidal chemicals, which can cause environmental pollution. The pigment producer Metschnikowia andauensis belongs to the antagonistic yeasts, but details of the mechanism by which it inhibits growth of other microbes are less known. Our results confirmed its antagonistic capacity on other yeast species isolated from fruits or flowers and demonstrated that the antagonistic capacity was well correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…The iron-binding molecule pulcherrimin was described a century ago, but it is still not known which genes are responsible for its production [ 17 ]. The production of pulcherrimin is strongly dependent on the composition of culture media and other culture cultivation factors [ 6 , 14 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The iron-binding molecule pulcherrimin was described a century ago, but it is still not known which genes are responsible for its production [ 17 ]. The production of pulcherrimin is strongly dependent on the composition of culture media and other culture cultivation factors [ 6 , 14 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…That is, the same yeast species can inhibit certain microbes, while others are not inhibited under the same environmental conditions. Alternatively, growth of a given species is inhibited at a lower pH, while not at a higher pH [54,55]. The results of Giobbe are in line with this, because she found that Pichia fermentans was effective on the surface of apples, while its inhibitory capacity disappeared on peaches [62].…”
Section: Yeasts and Yeast-like Fungi Can Have Growth Inhibitory Effects Against Toxin Producing Fungimentioning
confidence: 58%
“…The relation between pigment production and antagonistic capacity is supported by the fact that the pigment-less M. pulcherrima mutants lacked antifungal activity [50,88]. Further studies have suggested that Metschnikowia species were able to produce proteases, cell wall degrading enzymes, or the cells competed for nutrients and space, and all these capacities could also contribute to their antagonistic capacity [50,52,53,55,100].…”
Section: Growth Inhibition Happens Via Different Mechanismsmentioning
confidence: 97%
See 2 more Smart Citations